Autoimmune hepatitis in 828 Brazilian children and adolescents: clinical and laboratory findings, histological profile, treatments, and outcomes - Porta, Gilda (2019)
sentation, laboratory findings, histological profile, treatments, and outcomes of children andadolescents with autoimmune hepatitis.Methods: The medical records of 828 children and adolescents with autoimmune hepatitiswere reviewed. A questionnaire was used to collect anonymous data on clinical presentation,biochemical and histological findings, and treatments.Results: Of all patients, 89.6% had autoimmune hepatitis-1 and 10.4% had autoimmunehepatitis-2. The female sex was predominant in both groups. The median age at symptomonset was 111.5 (6; 210) and 53.5 (8; 165) months in the patients with autoimmune hepatitis1 and autoimmune hepatitis-2, respectively. Acute clinical onset was observed in 56.1% and58.8% and insidious symptoms in 43.9% and 41.2% of the patients with autoimmune hepatitis-1and autoimmune hepatitis-2, respectively. The risk of hepatic failure was 1.6-fold higher forautoimmune hepatitis-2. Fulminant hepatic failure occurred in 3.6% and 10.6% of the patientswith autoimmune hepatitis-1 and autoimmune hepatitis-2, respectively; the risk was 3.1-foldhigher for autoimmune hepatitis-2. The gamma globulin and immunoglobulin G levels were sig-nificantly higher in autoimmune hepatitis-1, while the immunoglobulin A and C3 levels werelower in autoimmune hepatitis-2. Cirrhosis was observed in 22.4% of the patients; biochem-ical remission was achieved in 76.2%. The actuarial survival rate was 93.0%. A total of 4.6%underwent liver transplantation, and 6.9% died (autoimmune hepatitis-1: 7.5%; autoimmunehepatitis-2: 2.4%).Conclusions: In this large clinical series of Brazilian children and adolescents, autoimmunehepatitis-1 was more frequent, and patients with autoimmune hepatitis-2 exhibited higherdisease remission rates with earlier response to treatment. Patients with autoimmune hepatitis-1 had a higher risk of death.